Transition to Fluid-Induced Limit Cycle Self-Excited Vibrations of a Rotor and Instability Threshold “Hysteresis” - Agnes Muszynska (International Journal of Rotating Machinery)
The transient process which starts at the instability threshold of a rotor rotating in a fluid environment, and ends up in the limit cycle of self-excited vibrations known as fluid whirl or fluid whip, is discussed in this paper. A one-lateral-mode, isotropic, nonlinear model of the rotor with fluid interaction allows for exact particular solutions and an estimation of the transient process. The fluid interacting with the rotor is contained in a small radial clearance area, such as in bearings, seals, or rotor-to-stator clearances, and its effects are represented by fluid film radial stiffness, damping, and fluid inertia rotating at a different angular velocities.